Immunological and bacteriological shifts associated with a flagellin-hyperproducing Salmonella Enteritidis mutant in chickens - Barbosa, Fernanda de Oliveira [UNESP]; Freitas Neto, Oliveiro Caetano de; Rodrigues Alves, Lucas Bocchini [UNESP]; Benevides, Valdinete Pereira [UNESP]; Secundo de Souza, Andrei Itajahy [UNESP]; Rubio, Marcela da Silva [UNESP]; Almeida, Adriana Maria de [UNESP]; Saraiva, Mauro Mesquita [UNESP]; Bruno de Oliveira, Celso Jose; Olsen, John Elmerdahl; Berchieri Junior, Angelo [UNESP] (Springer, 2020)
Salmonella Enteritidis causes infections in humans and animals which are often associated with extensive gut colonization and bacterial shedding in faeces. The natural presence of flagella in Salmonella enterica has been shown to be enough to induce pro-inflammatory responses in the gut, resulting in recruitment of polymorphonuclear cells, gut inflammation and, consequently, reducing the severity of systemic infection in chickens. On the other hand, the absence of flagellin in some Salmonella strains favours systemic infection as a result of the poor intestinal inflammatory responses elicited. The hypothesis that higher production of flagellin by certain Salmonella enterica strains could lead to an even more immunogenic and less pathogenic strain for chickens was here investigated. In the present study, a Salmonella Enteritidis mutant strain harbouring deletions in clpP and fliD genes (SE Delta clpPfliD), which lead to overexpression of flagellin, was generated, and its immunogenicity and pathogenicity were comparatively assessed to the wild type in chickens. Our results showed that SE Delta clpPfliD elicited more intense immune responses in the gut during early stages of infection than the wild type did, and that this correlated with earlier intestinal and systemic clearance of the bacterium.
Keywords: Flagellin; Poultry; Salmonellosis; Mutant; Deletion